(untitled) (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2024)
Laura Wood is an Ottawa-based artist who paints with gestural strokes to create elegant abstract compositions. Her paintings are evocative and emotive as she uses paint and colour to represent, as Wood describes, “what otherwise cannot be expressed with words.” Her process is intuitive as she is guided by the paint & chance happenings with colour mixing and form. Intentionality happens as she pauses between strokes. This dance back and forth between pure expression and thoughtful mark-making is how her works are created. Originally from Aurora, Ontario, Woods even at a young age had a rich interior life and art gave her a place to fully express all aspects of her internal experience. Her family’s encouragement led her to pursue her passions and she went on to study and a Bachelor of Fine Arts from the Ontario College of Art and Design University in Canada. She is currently represented in Ottawa, ON at Koyman Galleries.